2014
DOI: 10.1007/s10344-014-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

Home range and migration patterns of male red deer Cervus elaphus in Western Carpathians

Abstract: This study provides for the first time in the Carpathians analysis of spatial behaviour of 20 male red deer monitored during 2005-2013 using radio-telemetry. Two distinct spatial patterns were displayed in the same local population, i.e. residential and migratory. Residential annual home ranges were significantly smaller compared to migratory ones using both Minimum Convex Polygon and Kernel Home Range, due to periodic movement of migrants between distinct seasonal ranges. Residents remained in the same area t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 55 publications
3
35
0
1
Order By: Relevance
“…The area (ca 600 km 2 ) is characteristic by a mountainous terrain within the altitudinal range of 400-1318 m determining two major climate zones used by red deer (Fig. 1; Kropil et al 2015). First, the moderately warm and humid climate in lower parts of the area ( 700 m a.s.l.)…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The area (ca 600 km 2 ) is characteristic by a mountainous terrain within the altitudinal range of 400-1318 m determining two major climate zones used by red deer (Fig. 1; Kropil et al 2015). First, the moderately warm and humid climate in lower parts of the area ( 700 m a.s.l.)…”
Section: Study Areamentioning
confidence: 99%
“…Within a geographic information system (GIS), locations of sample plots were selected randomly within the five habitats types in roadaccessible areas (i.e. within 500 m) known to be used by red deer (Kropil et al 2015). Crop fields were not sampled because they were known to have comparable amounts of biomass as pastures (Borowik et al 2013), comprised only 2.4% of the study area, and were considered unimportant as habitat for red deer in this area (Kropil et al 2015).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial confirmation of this assumption is that the results from our previous study showed that in the eastern Sudety Mountain region the proportion of area damaged by deer was the lowest at <600 m ASL and damage increased considerably with altitude. If we assume, based on other studies, that red deer density below and above 600 m ASL was similar, the variability in natural forage availability or quality, snow depth and energetic constrains may explain the altitudinal differences in deer pressure exerted on forest stands. It is also possible that at low elevation deer were stressed due to high pressure from settlements, agriculture and hunters, which limited their activity and pressure …”
Section: Discussionmentioning
confidence: 96%
“…Migrating individuals overcome the transition from winter to summer (and vice versa) significant distances. Roe deer (Capreolus capreolus), fallow deer (Dama dama), wild boar (Sus scrofa), and red deer (Cervus elaphus) are the flagship game species in Slovakia (Kropil et al, 2015).…”
Section: Demands Of the Mammal Species For Migrationsmentioning
confidence: 99%